О псевдоаналитичности непрерывных функций, обладающих σ-консерватизмом углов - Бондарь, А.В.; Лукьянова, Е.А. (Український математичний журнал, 1993)
We prove a theorem that a continuous function satisfying the condition K′σ, which is a generalization of the well-known D. B. Men'shov condition from the theory of analytic functions, is pseudo-analytic.